Growing lupine and vetch in mixed crops - Andrey V. Bezgodov; Konstantin A. Maron (Acta Biologica Sibirica, 2022)
This paper aimed to determine the efficiency of growing spring vetch and narrowleaf lupine in mixed crops to produce grain forage. Further, the paper evaluated the influence of seeding quantities, component ratios, and weather conditions on yield and reaction in agrophytocenosis. Field tests and results processing complied with the appropriate methods. The paper examined weather conditions, quality of grain forage, yield, land equivalent ratio, competitiveness, and aggressivity of crops. Land equivalent ratio (LER) reached 1.41 to 1.77 when planting mixed legume grains at seeding quantity of 0.9 to 1.4 germinating seeds per hectare, where vetch amounts to 32%–42% of lupine content (0.38–0.45). The research demonstrated the resilience of crops to lodging and their suitability for thrashing. Under favorable humidification (Selyaninov hydrothermal coefficient (SCC) at 1.6), narrowleaf lupine grains constitute the bulk of the yield (65%), while at less favorable humidification (SCC 0.62), spring vetch generates most of the yield (80%). Neither crop demonstrates a significant advantage under moderately arid conditions. under unfavorable weather conditions, the competitiveness of vetch (CRba) relative to lupine elevates from 1.8 to 7.3, while its aggressiveness (CAba) decreases from 4.9 to 1.6. This suggests that there is positive alleopathy and environmental tolerance in lupine and vetch agrophytocenosis. The research demonstrated the possibility of efficiently growing spring vetch and narrowleaf lupin in mixed crops in the Middle Urals to produce high-protein grain concentrate. Further, the research established the optimal seeding quantity and component ratio and evaluated the influence of weather conditions on yield and changes in the proportion of harvested crops.